2012
DOI: 10.1007/s11145-012-9387-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond spelling: the writing skills of students with dyslexia in higher education

Abstract: To have a clearer idea of the problems students with dyslexia may face during their studies, we compared writings of 100 students with dyslexia and 100 age matched control students in higher education. The aim of this study was to compare the writing of young adults with dyslexia and young adults without dyslexia. The study was carried out in Belgium with writers of Dutch. First, we studied the number and type of spelling errors, the quality of the texts produced, the use of words, and the handwriting, both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 19 publications
8
51
0
8
Order By: Relevance
“…As such, we can have some confidence that the remaining group differences on the timed summary measure are not from the known group differences in reading or spelling (e.g., Deacon et al, ). This finding converges with the results of Tops et al (), who found that transcription difficulties did not explain all of the challenges with a timed summary measure in university students with dyslexia. Here, we extend this finding to university students with a history of reading difficulties.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, we can have some confidence that the remaining group differences on the timed summary measure are not from the known group differences in reading or spelling (e.g., Deacon et al, ). This finding converges with the results of Tops et al (), who found that transcription difficulties did not explain all of the challenges with a timed summary measure in university students with dyslexia. Here, we extend this finding to university students with a history of reading difficulties.…”
Section: Discussionsupporting
confidence: 91%
“…We initially scored the summaries according to the procedure in the manual; we were not able to produce an acceptable inter‐rater reliability with this approach. As such, we followed Tops et al's () scoring protocol. Both our measure and Tops et al's measure included a Readability and Handwriting Quality scale.…”
Section: Methodsmentioning
confidence: 99%
“…Among the several measures that can provide information about composition skills in writing, we chose structure because it is a skill common to both reading and writing. From the perspective of writing skills, this study is in line with Tops, Callens, Van Cauwenberghe, Adriaens, and Brysbaert's (2013) recommendations to: analyze students' composition skills, besides spelling; analyze writing skills developmentally; and explore writing skills in transparent orthographies. To analyze students' writing skills we chose a free-writing task, for three main reasons.…”
Section: Rationale and Research Hypothesesmentioning
confidence: 58%
“…Future research should focus on the spelling component of writing, and replicate this study with a dictation or copying task. Future researchers interested in writing composition skills should replicate this study and include more measures of composition: breadth of vocabulary, readability, and the like (Tops et al, 2013). Finally, the results of this study refer to a population with a medium-high socio-economic level.…”
Section: Stability Of Reading and Writing Parameters At Two Points Inmentioning
confidence: 91%
“…Such students are often termed “high‐functioning dyslexics” (e.g., Gallagher, Laxon, Armstrong, & Frith, ; Pedersen, Fusaroli, Lauridsen, & Parrila, ) because they have succeeded in being enrolled in educational institutions assumed to require good literacy skills, such as universities (e.g., Hatcher, Snowling, & Griffiths, ; Kirby, Silvestri, Allingham, Parrila, & La Fave, ). Studies of such students have shown, in line with the phonological deficit theory of dyslexia (Lyon, Shaywitz, & Shaywitz, ), that many high‐functioning dyslexic students experience persistent problems in phonological awareness (e.g., Gallagher et al, ; Hatcher et al, ; Parrila, Georgiou, & Corkett, ; Snowling, Nation, Moxham, Gallagher, & Frith, ), nonword reading (e.g., Re, Tressoldi, Cornoldi, & Lucangeli, ; Tops, Callens, Lammertyn, Van Hees, & Brysbaert, ), and spelling (e.g., Kemp, Parrila, & Kirby, ; Snowling et al, ; Tops, Callens, Van Cauwenberghe, Adriaens, & Brysbaert, ). In terms of reading, most studies have found word‐reading deficits and reading‐speed deficits to persist (e.g., Deacon, Cook, & Parrila, ; Re et al, ; Snowling et al, ), with reading comprehension assessments showing more variable results (e.g., Deacon et al, ; Re et al, ).…”
Section: Introductionmentioning
confidence: 86%